Caring Improvement with An Analysis of The Causes of Emotional Exhaustion in Professional Students - Putri, Prestasianita; Susanti, Ika Adelia; Afandi, Alfid Tri (Poltekkes Kemenkes Palu, 2023)
The demand for quality services to patients and families continues to increase, especially for nursing services, so it requires nurses who have good caring. Students of the nursing profession who are future nurse candidates, cannot be separated from these demands. These demands can have the potential to bring emotional exhaustion to students. Emotional exhaustion can be caused by social support, workload, and self-efficacy. The purpose of this study was to analyze the increase in caring based on the analysis of the causes of emotional fatigue in nursing profession students. The research design in this study is a quantitative method with a cross sectional approach. The population of this study is professional students in two institutions in Jember. The number of samples in this study was 150 respondents, with accidental sampling techniques. Data taken from this study are caring behavior, self-efficacy, support, workload, and emotional exhaustion. In general, the results of this study were found that there was a relationship between social support and emotional fatigue (p-value = <0.0000, B: -0.986), there was a relationship between workload and emotional fatigue (p-value = <0.0000, B: 0.372), there was no relationship between self-efficacy and emotional fatigue (p-value = 0.356, B: -0.84) and there was a relationship between emotional fatigue and caring behavior (p-value = 0.002, correlation coefficient: 0.112). Caring can be improved by means of support from students' families, educational institutions and places of practice and calculating the workload experienced by students when carrying out practice.